Prevalence of Congenital Birth Defects among Pediatric Patients of Interior Punjab - Azizullah Langah, Abid Hussain, Salman Baig, Sumaira Riffat, Jabbar Ahmed Qureshi, Uzma Afreen, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the prevalence of congenital birth defects among the pediatric patients of Sialkot. Methods: A descriptive cross-sectional study was conducted at the pediatrics medicine, pediatric surgery and obstetrics ward of Khawaja Muhammad Safdar Medical College and hospital Sialkot Pregnant women irrespective of the parity were enrolled in the study. Demographic variables, detailed history and examination before and after delivery were noted on a preformed proforma. The data was entered and analyzed through Statistical Package for Social Science (SPSS) version 20. p-value less than 0.05 was considered as significant. Results: The mean age of the pregnant mothers included in the study was 25.45 ± 5.12 The most common age group affected was having age more than 30 years (58.1%) and majority were multiparous (52.4%). Cousin marriage was the most common factor leading to birth defects among their children and the result was significant (p-value ≤0.05). The prevalence of congenital birth defect was 14.7%. The cleft palate was the most common anomaly followed by hydrocephalus, cleft lip, down syndrome, polydactyly, undescended testes, club foot, microcephaly, meningyomyelocele, ambiguous genitalia and bradydactyly. Conclusion: The prevalence of congenital birth defect was 14.7% and cleft palate was the most common anomaly followed by hydrocephalus and down syndrome. The most common associated factor was cousin marriages.